WAYS OF PREPARING FUTURE PRIMARY CLASS TEACHERS FOR CONSTRUCTIVE PEDAGOGICAL ACTIVITY (E Conference Zone, 2024)
In this article, future primary school teachers are given ways to properly organize a lesson and some recommendations. Ways to develop conditions for preparing future primary school teachers for constructive pedagogical activity are shown.